The Unilateral Arbitration Clause between Permissibility and Nullity - Mahmoud Jaradat, Nashat; JassimSarhan, Ghassan (Information Sciences Letters, 2022)
Researching the judicial applications of Arab countries to one of the issues that have occupied legal thoughts in the Western world for decades and still in one form or another, the so-called Unilateral Arbitration Clauses, we did not find a discussion of the applicability of this clause within the laws. Even though this condition takes a reasonable space of the legal arguments as previously mentioned, it has even become widely used in contracts, such as tenancy, contracting, and financial investments. The study showed that the above-mentioned clause has recently increased its use in financing contracts, especially with the increasing globalization of banking services and bank transfers. Although banks usually prefer to resort to traditional litigation, lack of similarity in the legal rules and judicial applications related to banking transactions and their difference from one country to another was a reason for the banks preference of resorting to arbitration. There is no examination of the legitimacy of an unequal or optional arbitration clause in Bahrain. Also, the Bahraini and Egyptian courts, to the best of our knowledge, did not decide whether it should be considered null or valid. The same case is applied to the French courts which have no cases that examined this type of clauses except for a case in 2006 and the other is a judgment close to the same issue on October 7, 2015, from the French Court of Cassation. The English and American courts were different; they examined this clause and had several judicial implementations due to the fact that most of the arbitration terms are either related to multinational companies operating within the framework of the Wall Street Stock Exchange in New York or those that stipulate the enforcement of British and Wales law on the provisions of the contract . However, many Arab countries, in general, as well as Bahrain and some Gulf countries, in particular, are seeking in their economic model to attract foreign investments and capital, especially those related to financial and banking industries, to diversify sources of income. The decision of investing or not investing the capital in a country is made by the judicial authority in terms of independence as well as the judicial application of legal texts as these factors are directly reflected in the desire to invest and show the possibility of protecting investors.

The Role of the Foreign Cause in the Exemption of the Marine Carrier from Liability in accordance with the Rotterdam Rules: A Comparative legal study - Harb, Mohamed (UAEU Law Journal, 2022)

Settlement of Disputes Arising from Documentary Credit Under National and International Regulations - Nour, Hoda Magdy (UAEU Law Journal, 2022)
The need Settlement of disputes arising from bank credit between national and international rules, protecting the interests of the bank and ensuring its financial rights before the debtor. As the Bank faces different technical and legal difficulties, as well as the multiplicity of legal adaptation, we deal with the rules governing banking accreditation from the point of pleadings law, and the methods of amicable settlement of these disputes and following, and compulsory execution. International efforts are taking the lead in establishing the technical regulation of bank accreditation and setting rules "DOCDEX" in 1997, and the 2015 amendments, which still need more as they do not provide a legal way to implement them. It is necessary to find out legal regulation at the domestic and international levels, which calls for the legislator to intervene to organize its rules and procedures. We have sought in this study to weave the legal entity to seize bank credit within the legally acceptable limits based on a system of seizure of the debtor with third parties against the background of the legal system of documentary credit and the relationships arising from it, and its financial and economic effects that go beyond the parties to the beneficiaries of companies, bodies, and economic institutions, As the matter still requires the existence of special legislation regulating the seizure of bank credit, to ensure the effectiveness of the guarantees surrounding the appropriations by the national legislator and at the international level. This would expand the insurance of bank credit so that the creditors recover their full right directly or by seizing the value of the credit, which calls for organizing this seizure with rules that consider the privacy of this seizure and its rules and are consistent with the required speed in such transactions in a way that protects the creditor from abuse, in a manner that ensures the observance of confidentiality, due process, and the spirit of banking work, anticipate the possible future that will witness the decline of documentary credit and replace it with electronic transactions, the establishment of specialized banking courts that save time and effort.

In-kind Execution of Contractual Obligations: Rule and Exceptions under the UNIDROIT Principles and the French Civil Code - Shandi, Yousef (UAEU Law Journal, 2022)
This research deals with the principle of in kind execution of contractual obligations and the exceptions thereto under the 2016 UNIDROIT Principles and the provisions of the French Civil Code created by decree of 10 February 2016, which amends the Law on Contracts and General Provisions and Proof of Obligations. Both the UNIDROIT Principles and the French civil law establish the principle of in kind execution; it applies to all types of contractual obligations. Nevertheless, the UNIDROIT Principles state five exceptions to this principle, namely: when performance is impossible in law or in fact; when performance is unreasonably burdensome or expensive; when the party entitled to performance may reasonably obtain performance from another source; when performance is of an exclusively personal character; or when the party entitled to performance does not require performance within a reasonable time. Also, the French Civil Code includes similar exceptions to the obligation to perform in kind, namely, if the in kind execution is impossible, and if there is an apparent in proportionality between the cost the good faith debtor would endure and the benefit the creditor would achieve from the in kind execution. This research aims to analyze and compare the provisions on in kind execution under the UNIDROIT Principles and French Civil Law, in order to identify the extent to which they are harmonious or different. Accordingly, the principle of in kind execution of contractual obligations, including the conditions of its application is analyzed in the first chapter. The second chapter tackles the exceptions to this principle, in terms of concept, conditions of application, the judge's authority and the parties’ freedom to exclude them

المسؤولية التضامنية في الشركة - ساعو, فريال; بايو, رانية (جامعة مولود معمري, 2022)
تعتبر المسؤولية التضامنية من الضمانات القانونية التي كرسها المشرع الجزائري لحماية الغير المتعامل مع الشركة، حيث تقوم على فكرة تقاسم الأعباء والديون بين الشركاء واتحاد ذمتهم المالية في سبيل تحقيق ذلك. تعتمد المسؤولية التضامنية على وجود الاعتبار الشخصي في الشركة، إذ أن الشركات القائمة على الاعتبار المالي يصعب تطبيق هذا النوع من المسؤولية عليها، بالنظر إلى اقتصار تحمل المسؤولية لدى الشريك بقدر الحصة المقدمة، على خلاف الشريك في شركات الأشخاص الذي يتحمل مسؤولية مطلقة، غير أن هذا القول لا يمنع تطبيق هذه المسؤولية على شركات الأموال بشكل نسبي في حالات محددة تتعلق بتواجدها ضمن وضعيات قانونية تستوجب إعمال المسؤولية التضامنية كما هو الشأن بالنسبة لبطلان الشركة وتصفيتها، أو بسبب حالات ترتبط بالمركز القانوني للشريك، الذي قد يتعرض عند مباشرته للنشاط في إطار الشركة إما للوفاة أو الانسحاب أو الإفلاس الأمر الذي يستدعي.
Keywords: Contrepartie personnelle; RSE; Responsabilité conjointe; Responsabilité sociale; Société en coentreprise; Société par actions; Société à responsabilité conjointe; Sociétés de capitaux; Sociétés personnelles; الاعتبار الشخصي; الشركة; المسؤولية الاجتماعية; المسؤولية التضامنية; شركات الأشخاص; شركات الأموال; شركة التضامن; شركة المحاصة; شركة المساهمة

The Right to Water in Investment Treaty Arbitration and Its Impact on Jurisdiction and Applicable Law - Geravand, Farshad (Public Law Researsh, 2022)
The right to water in investment arbitration has been one of the most contentious issues before investment arbitration tribunals in recent decades. The privatization of public services, including water and sanitation, and assigning them to foreign investors has caused the right to water as a vital benefit being repeatedly raised in investment arbitrations. However, due to tribunals’ narrow interpretation of jurisdiction and applicable law, this fundamental human right has been considered irrelevant and ignored, and this has fueled the legitimacy crises in investment arbitration. This research seeks to indicate the potentiality of more protection of the right to water through balancing the states international obligations in the two areas of investment law and human rights law. Proposed methods for integrating human rights with investment law include the correct interpretation of jurisdictional clauses and the applicable law based on the treaties interpretation principles, systematic integration and the inclusion of new clauses in investment agreements. طرح حق بر آب در داوری سرمایه‌گذاری یکی از مناقشه‌انگیزترین مباحث پیش روی دیوان‌های داوری در چند دهه اخیر بوده است. خصوصی‌سازی خدمات عمومی از جمله آب و فاضلاب و سپردن آنها به سرمایه‌گذاران خارجی موجب شده تا حق بر آب بعنوان یک منفعت عمومی و حیاتی بارها در داوری‌های سرمایه‌گذاری مطرح شود. با تفسیر مضیق محاکم از شروط صلاحیتی و قانون حاکم، این حق بنیادین بشری در برخی موارد نامربوط و نادیده تلقی شده و این امر به بحران مشروعیت در داوری سرمایه‌گذاری دامن زده است. این جستار می‌کوشد تا امکان حمایت بیشتر از حق بر آب را از طریق برقراری تعادل بین تعهدات بین‌المللی دولت‌ها در دو عرصه حقوق سرمایه‌گذاری و حقوق بشر نشان دهد و در پایان روش‌هایی را برای ادغام این دو از جمله تفسیر درست شروط صلاحیتی و قانون حاکم با تکیه بر اصول تفسیر معاهدات، تلفیق سیستمیک و گنجاندن بندهای جدید در موافقتنامه‌های سرمایه‌گذاری پیشنهاد کند.
Keywords: Applicable law; International Investment Arbitration; Jurisdiction; Right to Water; Systemic Integration; تلفیق سیستمیک; حق بر آب; داوری سرمایه‌گذاری بین‌المللی; شروط صلاحیتی; قانون حاکم

آليات تقييم الصيرفة الاسلامية في البنوك التجارية وتحدياتها -دراسة حالة البنك الوطني الجزائري - ساعد, بن; الحميد, عبد (Ibn Khaldun University of Tiaret, 2022)
يعتبر النظام المصرفي من بين الأسس التي يعتمد عليها النشاط الاقتصادي لأي مجتمع و ذلك بالنظر لأهمية الدور الذي يلعبه في المساهمة في إمداد النشاط الاقتصادي بالأموال، اللازمة من اجل تنميته و تطوي ره ، وقد اجمع الباحثون الاقتصاديون على أن من بين أسباب الأزمات المالية ترجع إلى الأسلوب الربوي المتبع من طرف البنوك التقليدية، خصوصا بعد أن ضربت الأزمة المالية العالمية عصب الاقتصاد الرأسمالي سنة 2008 وهزت اقتصاديات الدول وأضعفت البنوك التجارية خلافا عن البنوك الإسلامية والبنوك التجارية ذات الشبابيك الإسلامية ، ومن هذا المنطلق ازدادت الحاجة إلى وجود بنوك تعمل وفقا للشريعة الإسلامية والتي تقوم على أساس إلغاء الفائدة وعدم التعامل بالربا في تعاملاتها، ومنه فقد أصبحت هذه البنوك لاعبا مؤثرا وبارزا في اقتصاديات الدول الإسلامية و العالمية و التي من بينها الجزائر التي اتجهت هي الأخرى للدخول إلى عالم الصیرفة الإسلامية باعتمادها لافتتاح نوافذ إسلامية على مستوى البنوك العمومية. ومن خلال دراستنا توصلنا الى أن البنوك العمومية الجزائرية تحاول خوض تجربة فتح شبابيك إسلامية وقد خلصنا بأن اعتماد هذه البنوك على آلية التعامل بشبابيك تعمل وفق قواعد الشريعة الإسلامية في معاملاتها المالية من شأنه أن يحقق استقطاب ورضا الزبائن. The banking system is considered one of the foundations on which the economic activity of any society is based, given the importance of the role, it plays in helping to supply economic activity with the funds necessary for its operation. Economic researchers have agreed that among the causes of financial crises are due to the usurious method adopted by banks, especially after the global financial crisis hit the backbone of the capitalist economy in 2008, shook the economies of the countries, and weakened commercial banks unlike Islamic banks and commercial banks with Islamic windows From this point of view, the need has grown for the existence of bank operating in accordance with Islamic law, which is based on the abolition of interests in their financial transactions, these banks have become an influential and leading actor in the economies of Islamic countries including Algeria, which has also tended to enter the Islamic banking world by adopting it to open Islamic windows at the level of public banks. Through our study, we concluded that Algerian public banks are trying to live with the opening of Islamic counters, and we concluded that the dependence of these banks on the processing mechanism of counters that operate according to the rules of Islamic Sharia law in their financial transactions, would attract and satisfy customers.
Keywords: Banques commerciales; Banques islamiques; Fenêtres islamiques; Satisfaction client; البنوك الإسلامية; البنوك التجارية; النوافذ الإسلامية; رضا الزبائن

التزام العون الاقتصادي بالإعلام عن الأسعار والتعريفات - سكفال, عبد الجليل (مجلة البحوث في الحقوق والعلوم السياسية, 2022)
إن الإعلام بالأسعار والتعريفات التزام قانوني يقع على عاتق البائع من أجل تبصرة المستهلك حتى يكون على علم بما سيقدم له من تعاملات بشكل علني وواضح بهدف إضفاء الشفافية على الممارسات التجارية ، ويتحقق الإعلام بمجموعة من الوسائل العامة وأخرى خاصة نص عليها المشرع الجزائري في القانون 04/02 الذي يحدّد القواعد المطبقة على الممارسة التجارية،كما أن الإخلال بتنفيذ الالتزام بالإعلام يؤدي إلى ترتيب المسؤولية المدنية تتمثل في إمكانية إبطال عقد البيع الاستهلاكي على أساس نظرية عيوب الإرادة أو على أساس عدم العلم الكافي بالمبيع ، وأيضا إقرار المسؤولية الجزائية على كل مخالفي هذا الالتزام بعد إجراء المعاينة وضبط المخالفات من طرف الأشخاص المختصة بالمراقبة وبالتالي توقيع عقوبات جزائية فضلا عن الجزاء الإداري ، هذا من أجل المحافظة على التوازن في العلاقة التعاقدية بين المستهلك باعتباره الطرف الضعيف في العلاقة وبين المتعاملين الاقتصاديين من أجل إرساء أسس النظام العام الاقتصادي. Informing about prices and tariffs is a legal obligation that the seller has in order to inform the consumer so that he is aware of what will be dealt with in a public and clear manner with the aim of imparting transparency to commercial practices The media is verified by a set of public and private means that the Algerian legislator stipulated in law 04-02 witche spicifies the rules aplicable to commercial practice, also the failure to implement the obligation to the media leads to the arrangement of civil liability represented in the possibility of nullifying the consumy sale contract on the basis of theoty of defects of the will or on of the basis of insufficient knowledge of the sale, and also the recognition of criminal liability for all violators of this obligation after conducting the inspection and controlling the violation by the persons concerned whith control consequenlty, penal sanctions are imposed in addition to the administrative penality, in order to maitain balance in the contratctual relationship and the economic dealers in order to lay the foundations of the general economic order.
Keywords: Consumer; Droit de la consommation; Economic aid

الحماية المدنية لقواعد حوكمة الشركات التجارية المتعلقة بمحافظي الحسابات - معمر, خالد; شارف, بن يحي (مجلة البحوث في الحقوق والعلوم السياسية, 2022)
يتضمن هذا البحث الحديث عن موضوع مهم جدا في مسألة حوكمة الشركات التجارية وهو إظهار مواطن التأثير من قبل محافظ الحسابات و إبراز مبادئ الحوكمة وتحقيقها في الشركة التجارية وما يتبعها من وعي لدى أصحاب المصالح وما ينتج عنه من زيادة الثقة في تعاملات الشركة وربحيتها ،لذلك تم الاهتمام بفحص النصوص المنظمة لتعيين محافظي الحسابات وبيان مهامهم ومسؤولياتهم وتقدير كفاية الحماية المدنية التي تحتوي عليها هذه النصوص ومدى ملاءمتها وخدمتها لقواعد الحوكمة. ومن ناحية أخرى حوكمة المسؤولية في حد ذاتها من خلال توقيعها على محافظي الحسابات الذين يستحقون حقا المساءلة وإعفاء من قاموا بواجباتهم التي فرضها القانون على أتم وجه من خلال تكريس القواعد التي تعفي من المسؤولية والأخرى التي تأمنهم منها. This research includes talking about a very important topic in the issue of business governance, which is to show the influence of the portfolios of accounts and to highlight the principles of governance and its realization in the commercial company and the subsequent awareness of stakeholders and the resulting increased confidence in the company's dealings and profitability, so attention was paid to examining the texts governing the appointment of account governors and showing their functions and responsibilities and assessing the adequacy of civil protection contained in these texts and their suitability and service to governance rules. On the other hand, governance of responsibility per se by signing it to the auditors who truly deserve accountability and exempting those who have fully carried out their duties imposed by law by enshrining the rules that exempt them from liability and those from which they are safe.
Keywords: Comptable; Développement; Gouvernance d'entreprise; Responsabilité civile; التنمية; حوكمة الشركات; محافظ الحسابات; مسؤولية مدنية

دراسة تحليلية للبيئة اللوجيستية و البيئة القانونية للتجارة الالكترونية في الجزائر - بوسيف, عبد القادر أسامة; زاوي, أسماء (Ibn Khaldun University of Tiaret, 2022)
هدفت الدراسة الى تحليل كل من البيئة القانونية و البيئة اللوجستية و مدى تأثيرها على التجارة الالكترونية في الجزائر، وتوصلت الى أن البيئة القانونية هي جد مناسبة و تواكب العصرنة و ان التعديل الأخير في قانون التجارة الالكترونية أثمر عن مواد جد مناسبةومحفزة للتجارة الالكترونية في الجزائر، بالرغم من ذلك، لم تجد التجارة الإلكترونية بعد مكانتها في الجزائر ولم تحقق بعد الآن الانطلاقة المرجوة، يعود السبب في ذلك لكون البيئة اللوجستية لا تزال متأخرة و لا تواكب التطور الهائل الحاصل في هذا المجال، وأنه على الجزائر العمل على تطوير بيئتها اللوجستية بمسايرة التقدم التكنولوجي في العالم من أجل إعطاء دفعة للنهوض بهذا النوع من التجارة و إعتمادها كأسلوب حديث للتبادل التجاري في الجزائر. The study aimed to analyze both the legal environment and the logistics environment and their impact on e-commerce in Algeria. The study concluded that the legal environment is very suitable and keeps pace with modernity, and that the recent modification of the law on electronic commerce has resulted in very appropriate and stimulating articles for electronic commerce in Algeria. However, e-commerce has not yet found its place in Algeria and has not yet achieved the desired breakthrough, the reason is that the logistics environment is still lagging behind and not keeping pace with the enormous development of international e-commerce, and that Algeria should work to develop its logistics environment to keep pace with technological advances in the world in order to give impetus to the advancement of this type of commerce and its adoption as modern mode of commercial exchange in Algeria.
Keywords: Commerce électronique; Environnement juridique; Environnement logistique; Paiement électronique; البيئة القانونية; البيئة اللوجيستية; التجارة الإلكترونية; الدفع الإلكتروني

النظام القانون للمؤسسات الناشئة في الجزائر - وناس, علي (Ibn Khaldun University of Tiaret, 2022)
الغاية من هذه الدراسة هو تسليط الضوء على المقاولاتية في مجال المال و الأعمال في عصرنة للنشاط التجاري بكل ركائزه منها ريادة الأعمال فظهرت المؤسسات الناشئة كخيار إستراتيجية انتهجته الجزائر و الذي فرضته العولمة و اقتصاد المعرفة المبني على تكنولوجيا المعلومات و الاتصال من أجل النهوض بالاقتصاد الوطني لتحقيق التنمية المستدامة بعيدا عن الريع. إن اهتمام الدولة بالمؤسسات الناشئة ككيان قانوني يختلف كليا عن الشركات التجارية التقليدية لأنها ترتكز على الإبداع و التكنولوجيا و سرعة النمو بأقل تكلفة، لذا خصها المشرع الجزائري بترسنة من النصوص القانونية لتحديد طبيعتها القانونية و توفير مناخ أعمال مناسب لنشاطاتها تجسدت في المرسوم التنفيذي رقم 20 - 254 المتعلق بإنشاء المؤسسات الناشئة و الحصول على علامة "مؤسسة ناشئة" و "مشروع مبتكر" و "حاضنة أعمال" و في القانون رقم 22 - 09 الذي حدد الشكل القانوني للمؤسسات الناشئة تحت عنوان "شركة المساهمة البسيطة". كما دعمها بآليات مختلفة تمثلت في صندوق خاص بتمويلها و حاضنات أعمال تسهر على تدريب فريق عملها و مرافقتها و متابعتها طيلة مراحل حياتها،إضافة إلى مزايا إعفاء جبائية. توصلت الدراسة إلى الاهتمام الكبير و الخاص بالمؤسسات الناشئة كونها الحل الاستراتيجي لتحريك عجلة التنمية الاقتصادية و تحقيق القيمة المضافة في الجزائر وضمان نجاحها. The purpose of this study is to shed light on entrepreneurship in the field of money and business in the modernization of commercial activity with all its pillars, including entrepreneurship. The emerging enterprises appeared as a strategic option adopted by Algeria, which was imposed by globalization and the knowledge economy based on information and communication technology in order to advance the national economy to achieve development sustainable without rent. The state’s interest in emerging enterprises as a legal entity is completely different from traditional commercial companies because they are based on creativity, technology and rapid growth at the lowest cost, so the Algerian legislator singled out them with an arsenal of legal texts to determine their legal nature and provide a suitable business environment for their activities embodied in Executive Decree No. 20-254 Related to the establishment of start-ups and obtaining the marks of “startup institution”, “innovative project” and “business incubator” and in Law No. 22-09 that defines the legal form of start-ups under the title “Simple Joint Stock Company”. He also supported her with various mechanisms represented in a special fund to finance her and business incubators that ensure the training of her work team, accompany her and follow up on her throughout her life, in addition to the advantages of a tax exemption. The study found a great interest in emerging institutions as a strategic solution to move the wheel of economic development and achieve added value in Algeria and ensure its success.
Keywords: Développement durable; Société par actions à responsabilité limitée; Startups; Économie de la connaissance; اقتصاد المعرفة; التنمية المستدامة; المؤسسات الناشئة; شركة المساهمة البسيطة

Role of Abuse of Rights Doctrine and Investment Arbitration Ratione Temporis in Limiting Nationality Planning - Saeedi, Niloofar; Askary, Pouria (Public Law Researsh, 2022)
Sometimes foreign investors after the dispute have arisen or when it is predictable and with the intention of bringing the dispute to arbitration, change their nationality or acquire new nationality. The phenomenon called Nationality Planning eases foreign investors’ access to a desirable treaty and increases the chance of bringing disputes against host states.So host states try to avoid these disputes by raising objections to Ratione Temporis or claiming abuse of rights. Arbitration tribunals’ approach towards their Ratione Temporis and abuse of rights is material in host states’ success in limiting Nationality Planning. So the question to be answered is that what requirements are considered by arbitrations in determining Ratione Temporis and abuse of rights and how these two are different. Arbitral precedent shows that these tribunals make distinction between cases of nationality planning contrary to their Ratione Temporis and cases that are considered as abuse of rights. However, in practice their strict approach results in limited acceptation of objections to Ratione Temporis or abuse of rights claims. گاه سرمایه‌گذار خارجی پس از بروز اختلاف یا زمانی که اختلاف قابل پیش‌بینی است و به قصد طرح دعوی در مرجع داوری، اقدام به تغییر تابعیت یا کسب تابعیت جدید می‌نماید. این اقدام که برنامه‌ریزی تابعیت نام دارد، دسترسی سرمایه‌گذار خارجی به یک معاهده سرمایه‌گذاری مطلوب را تسهیل کرده و احتمال طرح دعوی علیه دولت میزبان را افزایش می‌دهد. از این‌رو دولت‌های میزبان تلاش می‌کنند با طرح ایراد به صلاحیت زمانی یا سوء استفاده از حق، مانع پذیرش چنین دعوایی شوند. رویکرد مراجع داوری در احراز صلاحیت زمانی خود و تشخیص موارد سوء استفاده از حق، در موفقیت یا عدم موفقیت دولت میزبان در مقابله با برنامه‌ریزی تابعیت تعیین‌کننده است. بنابراین باید به این پرسش پرداخته شود که مراجع داوری چه شرایطی را برای احراز صلاحیت زمانی و سوء استفاده از حق در نظر می‌گیرند و چگونه میان این دو تمایز قائل می‌شوند. رویه مراجع داوری حاکی از آن است که این مراجع میان مواردی از برنامه‌ریزی تابعیت که مانع صلاحیت زمانی آن‌هاست و مواردی که سوء استفاده از حق تلقی می‌گردد، تمایز قائل می‌شوند. هرچند رویکرد سخت‌گیرانه آنها در عمل موجب می‌شود تنها در موارد محدودی ایراد به صلاحیت زمانی یا ادعای سوء استفاده از حق مورد پذیرش واقع شود.
Keywords: Abuse of rights; Bilateral Investment Treaty; Foreign Investment Arbitration; Nationality Planning; Ratione Temporis; برنامه‌ریزی تابعیت; داوری سرمایه‌گذاری خارجی; سوء استفاده از حق; صلاحیت زمانی; معاهده دوجانبه سرمایه‌گذاری

Scope of Obligation of the Host State for Protection of Foreign Investor in Armed Conflicts - Shahbazian, Abolghasem; Salimi, Sadegh (Public Law Researsh, 2022)
Measures taken by governments during armed conflict to safeguard their essential interests sometimes cause damages to foreign investors. The investors thus affected seek remedies in the arbitration tribunals invoking breach of host government obligations to protect investments. The host government also usually attempts to assert as defense non-precluded measures to prove its irresponsibility, or if it proves responsible, justify it by resorting to circumstances precluding wrongfulness in the customary international law. But since different courts do not consider the same requirements to invoke these rules, there is no certainty that the parties to the lawsuit will be able to invoke them and, as a result, the scope of government's obligations to protect the foreign investor during the armed conflict is obscure. To clarify the scope of the host government's obligations to protect the foreign investor during armed conflicts and balance the interests of the investor and the host government during the investment disputes arising from the armed conflict, this article explores the possibility and requirements of invoking circumstances precluding wrongfulness and non-precluded measures and the relationship between them. اقداماتی که دولت‌ها در زمان مخاصمات مسلحانه در جهت حفظ منافع اساسی خود انجام می‌دهند گاه موجب ورود خسارت به سرمایه‌گذاران خارجی می‌گردد. سرمایه‌گذاران آسیب‌دیده در محاکم داوری با استناد به نقض تعهدات حمایتی توسط دولت میزبان، خسارات وارده به خود را طلب می‌نمایند. دولت میزبان نیز معمولاً برای اثبات عدم مسئولیت خود به شرط اقدامات منع نشده مندرج در معاهده سرمایه‌گذاری استناد می‌کند و یا در صورت اثبات مسئولیت، به منظور توجیه آن به معاذیر رافع وصف متخلفانه در حقوق بین‌الملل عرفی متوسل می‌شود. اما از آنجا که محاکم مختلف، شرایط یکسانی را جهت استناد کشور میزبان به شرط اقدامات منع نشده و معاذیر رافع وصف متخلفانه در نظر نمی‌گیرند، قطعیتی در امکان استناد به آن‌ها وجود ندارد. در نتیجه، قلمرو تعهد دولت به حمایت از سرمایه‌گذار خارجی در زمان مخاصمات مسلحانه در هاله‌ای از ابهام فرو رفته است. این مقاله با هدف روشن ساختن قلمرو تعهد دولت میزبان به حفاظت از سرمایه‌گذار خارجی در هنگام مخاصمات مسلحانه و به منظور توازن منافع سرمایه‌گذار و دولت میزبان در دعاوی سرمایه‌گذاری ناشی از مخاصمات مسلحانه، امکان و الزامات استناد کشور میزبان به معاذیر عرفی رافع وصف متخلفانه و شرط اقدامات منع نشده و ارتباط میان آنها را مشخص می‌نماید
Keywords: Armed Conflicts; Customary International Law; Foreign investment; Interests of the Host State; Non-Precluded Measures; اقدامات منع نشده; حقوق بین‌الملل عرفی; سرمایه‌گذاری خارجی; مخاصمات مسلحانه; منافع دولت میزبان

Banks responsibility in the collection of the commercial paper contract - Al-Shawabkeh, Wa’ed (Al-Balqa Journal for Research and Studies, 2022)
The importance of studying this contract is to establish the legal nature of the bank’s responsibility when it fails to collect the value of the commercial paper, and to know the role and direction of the judiciary in that respect. The study relied on the element of analysis and education in a brief scientific way. The purpose of the study is to examine the legal basis for the Bank’s responsibility in the collection contract and the general provisions for this responsibility resulting for it, and to cover that responsibility in all its aspects. The study relies on the analytical method in order to achieve the purpose and objectives of the research, where the legal texts will be analyzed and practical results will be reached. In this research legal texts will be analyzed to reach scientific results, the study also reached results, including that there was no regulation from the Jordanian legislator for the collection, in addition to the overlapping of the agency and deposit contracts in the collection contract and that the bank’s responsibility towards its client is a contractual responsibility due to the nature of the relationship between them. The research recommends that the Jordanian Trade law should include special texts dealing with the collection contract, and that the judiciary be more present while evaluating the nature of the relationship and the basis of responsibility between the bank and its client, and it should be clearly stated that the bank may require the disqualification of itself from the liability resulting from collection contract.

Third Party Investment in International Commercial Arbitration - Ebrahimi, Seyed Sadegh; Boloori, Peyman; Solhchi, Mohammad Ali (Public Law Researsh, 2022)
International commercial arbitration imposes heavy costs to the parties involved. In this regard, one of the new phenomena in international commercial arbitration is "financing of court costs by a third party investor. There are several reasons for the emergence of a third party investor: 1- involved parties may not have the resources to pay for the costs of arbitration or they may be reluctant to use their funds to finance the litigation: 2. the uncertainty of receiving compensation as a result of paying the arbitration fees might encourage the parties to transfer this risk to a third party; 3. having its own advantages and disadvantages. Since the funder holds the power of the purse, TPF entails the risk of the control of the claim being transferred to the third party funder. We might ask whether international arbitration tribunals should examine the extent of the investor's influence in determining the allocation of costs or not. In addition, is it essential to disclose the third parties contracts confidential? Overall, it is concluded that those mentioned Tribunals should allocate and guarantee the arbitration cost and agree on disclosing of third parties fund contracts under urgent conditions by international arbitration tribunal. مراجعه به داوری تجاری بین المللی هزینه های کلانی را برای طرفین درگیر در فرآیند داوری به همراه دارد و تأمین این هزینه ها در خیلی از موارد به‌صورت مانع در مراجعه به داوری نمود پیدا می‌کند. در همین راستا یکی از پدیده‌های جدید در داوری تجاری بین المللی، «تأمین مالی هزینه دادرسی توسط سرمایه گذار ثالث» است. ظهور سرمایه گذار ثالث دلایل متعددی دارد؛ اولاً طرفین دعوی ممکن است فاقد امکانات مالی کافی برای هزینه های داوری باشند، ثانیاً ممکن است طرفین دعوی تمایلی به استفاده از منابع مالی خود برای تأمین مالی دادرسی پرهزینه نداشته باشند، ثالثاً عدم قطعیت ذاتی که در زمینه امکان اخذ خسارت در نتیجه دادرسی وجود دارد می تواند باعث تمایل طرف منازعه به انتقال این ریسک به شخص ثالث شود. پرسش این است که آیا محاکم تجاری بین‌المللی تعیین تخصیص هزینه‌ها بپردازد یا خیر؟ و آیا افشاسازی قراردادهای شخص ثالث ضروری می‌باشد؟ در نهایت این نتیجه حاص می‌شود که محاکم مذکور باید به تعیین تخصیص و تضمین هزینه‌های داوری پرداخته و از سویی با افشاسازی قراردادهای تامین مالی شخص ثالث در داوری تجاری بین المللی، در شرایط خاص و ضروری موافقت نمایند.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Cost Allocation; Disclosure; International Arbitration Tribunals; International commercial arbitration; Investments; Third Party Investment; Third parties; افشاسازی; تخصیص هزینه‌ها; داوری تجاری بین‌المللی; دیوان‌های داوری بین‌المللی; سرمایه‌گذاری شخص ثالث

A Legal Analysis of the Structure of Dispute Resolution Mechanisms of International Tax Agreements - Salehifar, Alireza (Public Law Researsh, 2022)
As international trade is expanding, international trade and tax disputes are increasing. Under international tax agreements, there are two mechanisms for the resolution of potential disputes between contracting States. These agreements mostly rely on a form of negotiation known as the “Mutual Agreement Process (MAP)” as the main mechanism for the settlement of disputes. During the last decade, the inclusion of “ad hoc arbitration” as a new dispute resolution mechanism in international tax treaties has become popular to augment the MAP. Iran has long concluded several international tax agreements with several countries for the avoidance of double taxation. Due to Iran’s macroeconomic policy for relying more on tax revenues as an alternative to revenues from the petroleum industry, it is important that the Iranian lawyers seek to focus more on tax law and tax dispute resolution mechanisms. The purpose of this article is to introduce and critically analyse the dispute resolution mechanisms of international tax agreements. In this article, to make some suggestions for the improvement of the dispute resolution system of tax treaties, the strengths and weaknesses of the MAP and ad hoc arbitration, will be scrutinised by adopting a descriptive-analytical approach. همسو با گسترش تجارت فراسرزمینی،‌ میزان دعاوی مرتبط با تجارت و مالیات‌های بین‌المللی نیز افزایش یافته است. در بسیاری از معاهده‌های مالیاتی بین‌المللی برای حل اختلافات، دو ساز و کار با عنوان «فرآیند توافق دوجانبه» و «داوری موردی» وجود دارد. فرآیند توافق دوجانبه که مبتنی بر مذاکره بین طرفین معاهده است بعنوان ساز و کار اصلی و داوری موردی هم که در یک دهه اخیر در این معاهده‌ها رواج یافته، بعنوان ساز و کار مکمل فرآیند توافق دوجانبه برای حل اختلافات استفاده می‌شوند. ایران از دیرباز جهت اجتناب از مالیات مضاعف، معاهده‌های مالیاتی متعددی را با کشورهای مختلف منعقد نموده است. همچنین سیاست کلان اقتصادی کشور در سال‌های اخیر مبتنی بر اتکای بیشتر به درآمدهای مالیاتی بعنوان جایگزینی برای درآمدهای نفتی بوده است. لذا اهمیت شناخت این نوع معاهده‌ها و‌ مکانیسم‌های حل و فصل اختلافات آنها برای حقوقدانان کشور بیش از پیش آشکار می‌شود. هدف این مقاله معرفی،‌ تحلیل و نقد ساز و کارهای موجود در معاهده‌های مالیاتی بین‌المللی برای حل اختلافات می‌باشد. در این مقاله نقاط ضعف و قوت فرآیند توافق دوجانبه و داوری موردی به شیوه توصیفی-تحلیلی بیان و راهکارهایی جهت بهبود این مکانیسم‌ها ارائه می‌شود.
Keywords: Arbitrage; Arbitragem; Arbitration; Dispute Resolution; International Tax Agreements; Mutual Agreement Procedure (MAP); Negotiation; داوری; فرآیند توافق دوجانبه; مذاکره; معاهده مالیاتی بین‌المللی; ‌ حل و فصل اختلاف

الحق المعنوي للفنان العازف أو المؤدي في قانون الملكية الأدبية والفنية - دراسة مقارنة - - بعديد, دلال (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
يعتبر الفنان العازف أو المؤدي، الطائفة الوحيدة من أصحاب الحقوق المجاورة التي تتمتع بحقوق معنوية ومالية على أعماله. فالطابع الإبداعي الذي يكتسيه أداؤه يبرز شخصيته الأدبية والفنية، على خلاف أعمال أصحاب الحقوق المجاورة التي تتسم بالطابع الصناعي اولمادي. يتضمن الحق المعنوي جملة من الصلاحيات تمكن الفنان من الاستفادة من أعماله وحمايتها من مختلف أنواع الاعتداء. غير أنها وإن كانت تتشابه في البعض منها مع الحقوق المخولة للمؤلف لحماية مصنفات ه وشخصه، إلا أنها تختلف معها في البعض منها لاسيما الحق في تقرير النشر، والحق في السحب أو الندم، باعتبار أن التشريعات الوطنية الخاصة بالحقوق المجاورة والتي اعترف ت للفنان التمتّع بحق معنوي ، جاءت خالية من الإشارة إلى ذلك. لذا كان من الضروري تحديد مدى تمتع الفنان العازف بهذين الحقين، أمام الف ا رغ القانوني الذي أدى إلى مجادلات فقهية وتضا رب في الأحكام القضائية. L'artiste interprète ou exécutant est le seul des titulaires de droits voisins à bénéficier d’un droit moral et d’un droit patrimonial sur son interprétation. Le caractère original de sa prestation met en valeur sa personnalité littéraire et artistique, à l’inverse des oeuvres des titulaires de droits voisins qui se caractérisent par leur aspect industriel et matériel. Le droit moral dont dispose l'artiste-interprète, comprend un ensemble de prérogatives qui lui permettent de bénéficier de ses oeuvres et de les protéger contre les divers abus. Cependant, et bien qu’elles soient similaires, pour certaines d’entre elles, aux droits octroyés à l’auteur pour protéger son oeuvre et sa personne, elles se différencient de certains d’entre eux, en particulier le droit de divulgation et le droit de retrait ou de repentir, du fait que les législations nationales relatives aux droits voisins qui reconnaissent à l'artiste la jouissance d’un droit moral, sont dépourvues de toute référence à ce sujet. Dès lors, il était nécessaire de déterminer dans quelle mesure l'artiste-interprète jouit de ses deux droits, face au vide juridique qui a donné lieu à des controverses doctrinales et à des décisions de justice contradictoires. The artist, musician or performer, is the only one of the holders of related rights to benefit from a moral right and financial rights over his performance. The original character of his performance highlights his literary and artistic personality, unlike the works of holders of neighboring rights which are characterized by their industrial and material aspect. The moral rights available to the performer include a set of prerogatives that allow them to benefit from their works and protect them against various abuses. However, and although they are similar, for some of them, to the rights granted to the author to protect his work and his person, they are different from some of them, in particular the right of disclosure and the right of withdrawal or of repentance, due to the fact that national laws relating to neighboring rights which recognize the artist's enjoyment of a moral right, are devoid of any reference to this subject, Therefore, it was necessary to determine to what extent the performer enjoys both rights, in the face of the legal vacuum which has given rise to doctrinal controversies and contradictory court decisions.
Keywords: Arbitrage; Arbitration; Artist interpréter; Artist performer; Artiste exécutant; Artiste interprète; Contrefaçon; Counterfeiting; Droit moral; Intellectual property; International protection; Moral right; National protection; Piracy; Piratage; Propriedade intelectual; Propriété intellectuelle; Protection internationale; Protection nationale; Responsabilité; Responsibility

ال رقابة القضائية على أحكام ال ت حكيم دراسة مقارنة في القوانين العربية - زريفي, محمد (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
إن كان التحكيم طريقا بديلا للقضاء في حسم المنازعات، فإن عملية التحكيم تحتاج لكي تكتمل أسباب فاعليتها وانفاذ أحكامها لتدخل قضاء الدولة باعتباره سلطة عامة، تملك قوة إل ا زم الخصوم بتنفيذ أحكام المحكمين. ومن باب المفارقة، أن هذه الرقابة القضائية على أحكام التحكيم، تؤدي إلى إقحام القاضي الوطني في ن ا زع، أستبعد منه مسبقا بإ ا ردة المتنازعين، إلا أن المفارقة ظاهرية، حيث أن دور القاضي يبقى منحص ا ر في رقابة مدى مطابقة الحكم التحكيميي لمبادئ أساسية، أتت على سبيل الحصر، دون أن يكون له فحص وقائع وموضوع الن ا زع. غير أن تحديد سلطة القاضي لي س مطلقة، فبناء على المقاربة الجديدة المبنية على نوع المصالح المطلوب حمايتها، كمعيار لتحديد درجة وشدة الرقابة المسلطة على حكم لتحكيم، يستطيع هذا الأخير، تعديل رقابته بين مشددة ومخففة . وعلى هذا الأساس، فإن غالبية القضاءات العربية تبنت موقفا وسطيا بين مذهبي التوسع والتضييق من نطاق رقابة المحاكم على حكم التحكيم الدولي، تماشيا مع متطلبات التجارة الدولية ومقتضيات مصالحها الوطنية . If arbitration is an alternative means of resolving disputes, the arbitration process needs, for the reasons of its effectiveness and the application of its provisions, the intervention of the judicial power of the State, in order to oblige the parties to carry out the arbitral awards. Paradoxically, this judicial review of arbitral awards leads to involving the national judge in a dispute, which was previously excluded by the will of the parties in dispute. However, this paradox is apparent, because the role of the national judge remains limited to the strict control of the compliance of the arbitration award with the basic principles enacted in an exclusive manner, without having to examine the facts and the subject of the dispute. However, this limitation of judicial power is not absolute, because on the basis of the new approach, based on the type of interests to be protected, as the criterion for determining the extent of the control exercised over an arbitral award, the latter can modulate its control between strict and attenuating. On this basis, the majority of Arab jurisdictions have adopted a middle position between the two tendencies, so-called maximalist control, and minimalist tendency of the jurisdictions' control over the international arbitration award, in accordance with the needs of international trade and the requirements of their interests. Si l'arbitrage est un moyen alternatif pour de résoudre les différends, le processus d'arbitrage a besoin, pour les raisons de son efficacité et l'application de ses dispositions de l'intervention du pouvoir judiciaire de l'État, afin d'obliger les parties d'exécuter les sentences arbitrales. Paradoxalement, ce contrôle judiciaire sur les sentences arbitrales conduit à impliquer le juge national dans un litige, qui en était auparavant exclu par la volonté des parties en litige. Toutefois, ce paradoxe est apparent, car le rôle du juge national reste limité au strict contrôle de la conformité la sentence arbitrale aux principes de base édicté d’une manière exclusive, sans avoir à examiner les faits et l'objet du litige. Cependant, cette limitation de pouvoir juge n'est pas absolue, car sur la base de la nouvelle approche, fondée sur le type d'intérêts à protéger, comme critère de détermination de l'étendue du contrôle exercé sur une sentence arbitrale, ce dernier peut moduler son contrôle entre strict et atténuant. Sur cette base, la majorité des juridictions arabes ont adopté une position médiane entre les deux tendances, contrôle dite maximaliste, et tendance minimaliste du contrôle des juridictions sur la sentence d'arbitrage international, conformément aux besoins du commerce international et aux exigences de leurs intérêts.
Keywords: Arbitrage international; Arbitration; Commerce international; Contrôle des juridictions; International Trade; International arbitration award; Sentence arbitrale